Child’s Playing Perception in Settlement Public Space in Yogyakarta - Rini Darmawati; Hastuti Saptorini (Departement of Architecture, Universitas Islam Indonesia, 2018)
Preference discrepancy of playground between user (Children) and planners still found in several housing and settlement in Yogyakarta . This happens because of the Choice Model which means that each person and group has a choice of different models especially for children. This paper is an embodiment of the research of the author with the title “Children’s Perception of the Playroom with a Review of Comfort and Security. Case Study in Blimbingsari, Cokrodiningratan and Kotagede Hamlets in Yogyakarta City”. Through the graphic / drawing method, children convey their perceptions to express the desire to play in the public space. Equipped with some pictures documentation of children’s behavior playing, the author studied it uses persepsional analysis to find models of children’s desires for the playroom. The results of the study found that there are 5 elements that express children’s expectations in play, namely communal community, play settings that are full of natural elements, there are tools / media as play media, public amenities as a magnetude gathering of children, and the last element is that children are conducive and safe playing when there is free time and air is comfortable, namely during holidays and afternoons.Keyword: Children’s perceptions, children’s pictures, playing elements